A Novel Two Switch Non-inverting Buck-Boost Converter based Maximum Power Point Tracking System - Khandker Tawfique Ahmed; Mithun Datta; Nur Mohammad (International Journal of Electrical and Computer Engineering (IJECE), 2013)
A solar module can’t transfer maximum power to the load itself due to impedance mismatch. A maximum power point tracking (MPPT) system could be employed to have the maximum power.  A new MPPT system has been developed using Buck-Boost type DC-DC converter. The system is highly efficient and robust. PIC16F73 microcontroller has been used to control the DC-DC converter output. PV module output power is measured using microcontroller. The output power is compared with the previous module output power and the duty cycle of the converter is adjusted continuously to track MPP.  This process repeats until the output power reaches near to the maximum power point.In this paper, a maximum power point tracking (MPPT) system is developed using  two-switch non-inverting buck-boost converter. Perturb and observe (P & O) MPPT algorithm is used to transfer maximum power from the PV panel which is executed using a microcontroller.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2772